2019
DOI: 10.1016/j.actbio.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

72-Hour in vivo evaluation of nitric oxide generating artificial lung gas exchange fibers in sheep

Abstract: The large, densely packed artificial surface area of artificial lungs results in rapid clotting and device failure. Surface generated nitric oxide (NO) can be used to reduce platelet activation and coagulation on gas exchange fibers, while not inducing patient bleeding due to its short half-life in blood. To generate NO, artificial lungs can be manufactured with PDMS hollow fibers embedded with copper nanoparticles (Cu NP) and supplied with an infusion of the NO donor S-nitroso-Nacetyl-penicillamine (SNAP). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Thus, coatings will have limited benefit when the remainder of the circuit, particularly the circuit inlet, are rapidly producing thrombus. In a similar study using ECMO without anticoagulation, Lai et al found a precipitous increase in failure rate at around 36 hours, even in devices with relatively slower clot formation [30].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, coatings will have limited benefit when the remainder of the circuit, particularly the circuit inlet, are rapidly producing thrombus. In a similar study using ECMO without anticoagulation, Lai et al found a precipitous increase in failure rate at around 36 hours, even in devices with relatively slower clot formation [30].…”
Section: Discussionmentioning
confidence: 93%
“…Lai et al. showed that fibres that release nitrogen oxide may be used on gas exchangers to reduce platelet activation and thrombosis without causing bleeding, which provides new insight into anticoagulation improvement during ECMO [ 76 ].…”
Section: Reviewmentioning
confidence: 99%
“…Surface-generated nitric oxide (NO) is used to reduce the platelet activation and coagulation on fibers. Approach [140] using PDMS hollow fibers embedded with copper nanoparticles (Cu NP) infused into the NO donor S-nitroso-N-acetyl-penicillamine to reacts with Cu NP to generate NO has shown potential. Although a reduction in blood clotting is observed, it dampens the oxygen transfer by 13.3% compared to baseline.…”
Section: Total Artificial Lungmentioning
confidence: 99%